The Emerging Immunological Role of Post-Translational Modifications by Reactive Nitrogen Species in Cancer Microenvironment - De Sanctis, Francesco; Sandri, Sara; Ferrarini, Giovanna; Pagliarello, Irene; Sartoris, Silvia; Ugel, Stefano; Marigo, Ilaria; Molon, Barbara; Bronte, Vincenzo (Frontiers in Immunology, 2014)
Under many inflammatory contexts, such as tumor progression, systemic and peripheral immune response is tailored by reactive nitrogen species (RNS)-dependent post-translational modifications, suggesting a biological function for these chemical alterations. RNS modify both soluble factors and receptors essential to induce and maintain a tumor-specific immune response, creating a “chemical barrier” that impairs effector T cell infiltration and functionality in tumor microenvironment and supports the escape phase of cancer. RNS generation during tumor growth mainly depends on nitric oxide production by both tumor cells and tumor-infiltrating myeloid cells that constitutively activate essential metabolic pathways of L-arginine catabolism. This review provides an overview of the potential immunological and biological role of RNS-induced modifications and addresses new approaches targeting RNS either in search of novel biomarkers or to improve anti-cancer treatment.